2006
DOI: 10.1128/mcb.26.8.2936-2946.2006
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Regulates Spatial Memory Formation and Synaptic Plasticity through Protein Kinase A/CREB Signaling

Abstract: Synaptic activity-dependent de novo gene transcription is crucial for long-lasting neuronal plasticity and long-term memory. In a forebrain neuronal conditional NF-κB-deficient mouse model, we demonstrate here that the transcription factor NF-κB regulates spatial memory formation, synaptic transmission, and plasticity. Gene profiling experiments and analysis of regulatory regions identified the α catalytic subunit of protein kinase A (PKA), an essential memory regulator, as a new NF-κB target gene. Consequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
165
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(169 citation statements)
references
References 65 publications
3
165
0
1
Order By: Relevance
“…In fact, a transgenic line expressing the super-repressor, IkBa-SR, predominately in interneurons, leads to a hyperexcitable state characterized by increased long-term potentiation, spatial learning, and seizures (O'Mahony et al, 2006). Perhaps not surprising, a transgenic line expressing the Tet-O inducible superrepressor under the CamKII-a promoter, shows opposite behavioral changes, namely deficits in spatial learning (Kaltschmidt et al, 2006). These behavioral deficits were accompanied by impaired long-term potentiation and reduced forskolin-induced CREB phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a transgenic line expressing the super-repressor, IkBa-SR, predominately in interneurons, leads to a hyperexcitable state characterized by increased long-term potentiation, spatial learning, and seizures (O'Mahony et al, 2006). Perhaps not surprising, a transgenic line expressing the Tet-O inducible superrepressor under the CamKII-a promoter, shows opposite behavioral changes, namely deficits in spatial learning (Kaltschmidt et al, 2006). These behavioral deficits were accompanied by impaired long-term potentiation and reduced forskolin-induced CREB phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…These researchers subsequently used this model to explore the relationship between NF-kB and synaptic activity-dependent transcription, which is crucial for long-lasting neuronal plasticity and long-term memory. NF-kB was found to regulate spatial memory formation by controlling the expression of the alpha catalytic subunit of protein kinase A, an important regulator of CREB (cAMP response element binding protein) signalling in this process (Kaltschmidt et al, 2006).…”
Section: Ijb Proteinsmentioning
confidence: 99%
“…On the other hand, RelA has been implicated in facilitating spatial memory formation and synaptic plasticity (Meffert et al, 2003), although it was suggested that inactivation of RelA might not be the only contributing factor to the memory defect of RelAÀ/ÀTNF-R1À/À mice, as TNF-R1 deficiency was previously described to alter synaptic plasticity in in vitro preparations (Albensi and Mattson, 2000). Further supporting a role for NFkB in learning and memory, neuronal ablation of NFkB by tetracycline-dependent expression of an IkBa super-repressor also gives rise to defects in spatial memory formation (Kaltschmidt et al, 2006). However, contrary to NF-kB's effects in response to stress or injury, its role in these physiological contexts seems to be independent of its effect on apoptosis, as RelAÀ/À TNF-R1-deficient mice or mice with targeted inhibition of NF-kB in the forebrain show normal CNS development and no defect in neuronal survival (Fridmacher et al, 2003;Meffert et al, 2003).…”
Section: Introductionmentioning
confidence: 99%